ENHANCEMENT OF CONCEPTION RATE BY GNRH WITH TAI IN REPEAT BREEDER COWS UNDER FIELD CONDITIONS - MURUGAVEL, K; HEMALATHA, H; KANTHARAJ, S; ANTOINE, D (The Indian Journal of Animal Reproduction, 2022)
Thirty three repeat breeder dairy cows maintained under field conditions and were inseminated at spontaneous estrus were utilized for the study. Cows in treatment group (n=16) were administered with 2.5 ml of injection Gonadotropin Releasing Hormone (GnRH) on the day of AI. Cows in control group (n=17) served as a control without any treatment. Blood samples were collected from all the cows on the day of AI and day 6 post-AI for serum progesterone estimation. Pregnancy diagnosis was done on 45th day post-AI. There is no significant difference in the serum progesterone concentration between the two groups on the day of AI but there was significant difference on day 6 post-AI. The overall conception rate obtained in control and treatment groups were 29.41 % and 43.75 % respectively.